P732 Endoscopic Balloon Dilation Of Symptomatic Intestinal Crohn's disease Strictures: Long-Term Data On Efficacy And Safety In A Cohort Of Patients Followed-up For 10 Years. (25th January 2019) - Scimeca, D; Mocciaro, F; Di Mitri, R; Giunta, M; Renna, S; Teresi, G; Conte, E; Bonaccorso, A; Casà, A; Cottone, M; Orlando, A
Abstract: Background: Crohn's disease (CD) is a chronic disease frequently complicated by obstructive symptoms secondary to development of intestinal strictures. In the medium-short-term period endoscopic through-the-scope (TTS) balloon dilation offered a valid therapeutic alternative in those with intestinal symptomatic strictures. Data on long-term efficacy and safety are still lacking. We present data from a cohort of CD patients treated with balloon dilation and followed for up to 10 years. Methods: In 2011 we published data on a cohort of CD patients with symptomatic naïve or post-operative intestinal strictures treated effectively with endoscopic TTS balloon dilation (1–2–3 years cumulative symptom-free rates of 76%, 55% and 46%). In this cohort last balloon dilation was performed in December 2008 and 4 out of 37 patients underwent surgery. We followed-up the remaining 33 patients to the present day. Data on obstructive symptoms relapse, hospitalisation, surgical recurrence and safety were collected. Results: We collected data on 28 out of 33 patients (5 patients were lost at the follow-up): 16 male (57%), 27/28 patients had a post-operative stricture. Twenty-three patients (82%) have suffered from a clinical relapse (obstructive symptoms) through the follow-up, while 5 (18%) were in clinical remission: 7 (25%) were treated with mesalamine/steroids as needed, 6 (21%) with immunosuppressants and 15 (54%) with biological therapies. Fifteen/23 symptomatic patients (65%) underwent a new balloon dilation: 1 dilation in 6 patients, 2 dilations in 4, and more than 2 dilations in the remaining 5 patients; no complications after the re-dilation were recorded. Eight/23 symptomatic patients (25%) did not undergo a new balloon dilation: 4 were treated conservatively (steroids) while 4 were operated-on due to severe intestinal obstruction not suitable for endoscopic dilation. In patients treated with a new dilation, 60% (9/15) avoided new surgery at the end of the follow-up (75.8 ± 38.9 months). Seventeen patients (61%) were hospitalised during the follow-up (in 10 patients hospitalisation was scheduled to perform surgical intervention rather than an obstructive flare). Final overall surgical rate was 36% (6 patients in those re-dilated and 4 in those not re-dilated) with 64% of patients 'free from surgery' with or without new endoscopic balloon dilations. Conclusions: Data from this long-term study shows that balloon dilation is an effective and safe procedure to treat CD symptomatic strictures. After an initial effective balloon dilation the sustained clinical benefit through the follow-up was over 60% considering that in those with obstructive symptoms relapse balloon dilation can be safely repeated limiting the need for surgery to just 1/3 of the patients.